Entrepreneurial intentions of Polish and Czech students – comparative studies - Adamek, Jacek; Krawiec, Wojciech; Solarz, Małgorzata (Intencje przedsiębiorcze polskich i czeskich studentów – studia porównanwcze, 2019)
The purpose of the article is to identify and analyse the factors influencing the entrepreneurial intentions of students at the Faculty of Economics, Management and Tourism of Wrocław University of Economics (FEMT) and the Technical University of Liberec (TUL). The research hypothesis adopted in the study stated that despite the geographical proximity of the carried out social functions, there occurs a large variety of motivation, personality and cultural factors influencing the entrepreneurial intentions of students from FEMT and TUL. The presented layout of the article and the applied research methods, such as the subject literature overview, descriptive and comparative analysis and survey research conducted using CAWI (Computer-Assisted Web Interview) method were used to achieve the defined objective and to verify the hypothesis. The analysis and interpretation of the research material allowed to confirm the adopted research hypothesis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 7-24
Keywords: entrepreneurship; entrepreneurial intentions; cultural differences; przedsiębiorczość; intencje przedsiębiorcze; różnice kulturowe